Developing a framework for streetscape design to promote walkability in Malaysian campus - Harun, Nor Zalina; Nashar, Amanina (American Scientific Publishers, 2017)
Campus physical environment plays a significant role in shaping the life of its community, particularly among students. A good campus is the one that supports the student’s social needs, health and wellbeing through proper campus planning and design. Campus planning and design include open spaces, landscape as well as other facilities such as the streetscape. This study content that good streetscape design in a campus is essential to facilitate student mobility and to support student’s social, health and wellbeing. Lack of concern for pedestrian needs and streetscape design that is not responding to the tropical climate seems to be the issue that requires the fullest attention in promoting walkability amongst students. This paper aims to overcome this shortcoming by developing a framework that can be applied to appraise streetscape design in a campus for walkability enhancement. An initial framework is developed using theoretical basis and is subsequently refined through a preliminary survey conducted in IIUM Gombak Campus. The study adopts a mixed method to select the most relevant factors, identified through document analysis and preliminary questionnaire survey while quantitative analysis is conducted to ascertain the ratings of the selected factors. Both approaches have yielded four walkability factors of comfort, connectivity, safety, and accessibility. 32 most relevant criteria are identified to enhance walkability among pedestrian around the campus. The framework, together with the identified factors and criteria, provides a valuable reference for campus development division to formulate design guidelines and implementation for the new streetscape design or upgrading purposes.